Journey of Recovery: Challenges and Coping Resources of a Cancer Survivor and Caregiver (Sains Humanika, 2025)
Living with cancer is challenging.  The journey of treatment and recovery can be a daunting experience for individuals with cancer as well as caregivers.  Studies have shown that cancer survivors’ coping strategies and the support received were keys to recovery.  Hence, this research aims to explore the challenges faced by cancer survivor and caregiver, their unmet needs, coping strategies, support and changes they have discovered during the recovery journey.  A qualitative research method was adopted where a cancer survivor and a caregiver were chosen purposively. Both of them were interviewed separately in order to understand their experience in an in-depth manner.  The data was transcribed and analysed with thematic analysis aided by Nvivo 12. Data was triangulated through member checking, informants’ and experts’ validation. Informal observation, newspaper articles and social media communication were referred to ensure the trustworthiness of the data.  The findings show that both cancer survivor and caregiver were overwhelmed with negative emotions.  However, both parties entrusted their beliefs to God and combated the disease with perseverance and optimism. Their personality, coping strategies and support received from family, friends and communities were their main resources. This study suggests that forming supportive communities and involving mental health professionals enable both individual with cancer and caregiver to face the disease in a more proactive manner.
Keywords: Cancer survivor, caregiver, challenges, cope with cancer, resources, qualitative research